Pengujian Sistem Pengendalian Temperatur pada Prototipe Heat Exchanger Berbasis PID - Wardhana, Asepta Surya; Amelinda Azizah, Hana; Hamdani, Chalidia Nurin (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2021)
The design of a PID-based heat exchanger temperature control system means controlling the temperature of the cold water output of the heat exchanger that has been designed to match the set point value through PID (Proportional Integral Derivative) controller mode control. Temperature control is carried out by controlling the flow rate of hot water. When the set point of the heat exchanger cold water temperature is increased, the servo valve opens more so that the hot water flow rate increases. The system interface is done through Delphi 7 software which displays the display of numbers and graphs of the received process data. The PID controller mode parameter value is obtained through trial and error method. As a comparison, the ideal PID calculation is carried out using the direct synthesis method to be applied to the calculation of system control in the Arduino microcontroller. The ideal PID calculation requires bump test results from each process variable. The results of data analysis and interface graphs show that an increase in the set point from 25℃ to 32℃ at the temperature of the heat exchanger output water causes the servo valve opening to approach full opening and is in a hunting system condition when the temperature has reached the set point. From the test results obtained Time Constant 89.744 seconds, Settling Time 127.232 seconds and Rise Time 127.8 seconds.